2015
DOI: 10.1039/c5ta03974f
|View full text |Cite
|
Sign up to set email alerts
|

Si nanoparticles adhering to a nitrogen-rich porous carbon framework and its application as a lithium-ion battery anode material

Abstract: In this work, a novel Si/nitrogen-rich porous C composite was prepared by the simple co-assembly of gelatin, nano-CaCO 3 particles and Si nanoparticles, followed by a pyrolysis process and a subsequent acid washing treatment to remove the template. The Si nanoparticles were adhering to the nitrogen-rich porous carbon framework, which possesses good conductivity and adequate free space to accommodate the volume change of Si nanoparticles during cycling. By contrast with the bare Si nanoparticles and the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…The peaks of C 1s at 283 eV and N 1s at 398 eV can be attributed to the carbonized gelatin binder. The carbon containing nitrogen is believed to be beneficial for electrochemical performance [31]. The results of the XPS spectra are consistent with that of XRD and Raman analysis.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The peaks of C 1s at 283 eV and N 1s at 398 eV can be attributed to the carbonized gelatin binder. The carbon containing nitrogen is believed to be beneficial for electrochemical performance [31]. The results of the XPS spectra are consistent with that of XRD and Raman analysis.…”
Section: Resultssupporting
confidence: 87%
“…The Si-PV electrode displays rapid capacity decay with negligible capacity retention (below 50 mA h g À1 ) even after 4 cycles. It is demonstrated that PVDF binder is not able to adapt to the large volume change of silicon during cycling for its weak adhesion strength to silicon via van der Waals force [20,31]. According to above-mentioned Raman spectra for the Si-g-4 electrode, there remains organic substance after heat treatment, which may have a negative impact on the conductive performance and makes it show a poor cycle performance.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with the SiO 2 @C, the SiO 2 /po‐C@C composite has a reversible capacity of 669.8 mA h g −1 after 100 charge and discharge cycles with a high capacity retention rate of 98.6 %, showing a significantly improved cycling performance. The reason why the SiO 2 /po‐C@C performs the excellent cycling performance is that during the insertion and extraction of lithium ions, the buffering effect of void and carbonaceous matrix not only accommodate the volume expansion and shrinkage of SiO 2 , but also prevent the pulverization of the SiO 2 /po‐C@C particles, which make the electrode materials well contact with the current collector . Moreover, the lithium silicates (Li 2 Si 2 O 5 and Li 4 SiO 4 ) also adjust the volume change of Li x Si y alloy formed in the lithiation of SiO 2 .…”
Section: Resultsmentioning
confidence: 99%